THE INFLUENCE OF GIVING THE METHOD OF EXTENSION TO KNOWLEDGE MOTHER OF TODDLER ABOUT STUNTING - Kisman Kisman; Timbul Supodo; Sanihu Munir; La Banudi (Jurusan Gizi Poltekkes Kemenkes Makassar, 2020)
Stunting is a disease that during the last 10 years in Southeast Sulawesi showed a significant increase in prevalence. Various programs have been launched to reduce the incidence of this case and some regions have shown a decline. However, the decrease that occurred was very small, therefore it needed an appropriate method so that the stunting eradication program could be implemented properly. This study aims to determine the effect of providing counseling methods on the knowledge of mothers of children under five about stunting. Counseling methods used in this study are simulation, leafleat and individual or individual methods. This type of research is a quasi-experimental, which consists of four groups, namely groups given counseling with simulation methods, leafleats, individuals and groups that are not given treatment. The population in this study were all mothers of stunted children of 84 people. The sample size was 57 respondents, taken by proportional stratified random sampling. Data were analyzed descriptively and inferentially. The results showed that there was an effect of counseling by simulation and leafleat methods (p-value <0.05) on the mother's knowledge of stunting while the individual method had no significant effect on the mother's knowledge of stunting (p-value = 0.107> 0.05) . Therefore, the simulation and leafleat counseling methods are expected to be one of the counseling methods in implementing stunting eradication.